2023
DOI: 10.1098/rspb.2022.1784
|View full text |Cite
|
Sign up to set email alerts
|

Queens control caste allocation in the ant Cardiocondyla obscurior

Abstract: Social insect queens and workers can engage in conflict over reproductive allocation when they have different fitness optima. Here, we show that queens have control over queen-worker caste allocation in the ant Cardiocondyla obscurior , a species in which workers lack reproductive organs. We describe crystalline deposits that distinguish castes from the egg stage onwards, providing the first report of a discrete trait that can be used to identify ant caste throughout pre-imaginal develo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 98 publications
1
14
0
Order By: Relevance
“…In contrast, all untreated, presumed worker-destined eggs developed into workers, indicating that worker-destined eggs are more easily identified than queen-destined eggs and/or more likely to end up in experiments because they outnumber queen-destined eggs in stock colonies. The accuracy of caste prediction in early developmental stages furthermore appears to be influenced by sampling precision, as a previous study showed higher prediction accuracy rates for queen-destined eggs, but lower rates for queen-destined first instar larvae (Schultner et al 2023). Caste prediction accuracy was lowest for methoprene-treated worker-destined eggs, but still relatively high at 80% (12/15), suggesting minor, if any, effects of methoprene on caste once it can be identified by caste-specific crystalline deposits.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…In contrast, all untreated, presumed worker-destined eggs developed into workers, indicating that worker-destined eggs are more easily identified than queen-destined eggs and/or more likely to end up in experiments because they outnumber queen-destined eggs in stock colonies. The accuracy of caste prediction in early developmental stages furthermore appears to be influenced by sampling precision, as a previous study showed higher prediction accuracy rates for queen-destined eggs, but lower rates for queen-destined first instar larvae (Schultner et al 2023). Caste prediction accuracy was lowest for methoprene-treated worker-destined eggs, but still relatively high at 80% (12/15), suggesting minor, if any, effects of methoprene on caste once it can be identified by caste-specific crystalline deposits.…”
Section: Resultsmentioning
confidence: 98%
“…Across all developmental stages and treatments, a higher proportion of queen-destined compared to worker-destined individuals survived until pupation (queen-destined: 44.5% (346/893), worker-destined: 38.1% (321/868); Fisher’s exact test, odds ratio=0.770, p=0.008); this was mostly driven by differential survival of castes in the third larval instar (Table 1). Adult workers do not discriminate between developing queens and workers (Schultner et al ., 2023), so differential treatment is unlikely to explain this difference. Instead, increased survival of queen-destined larvae may stem from size differences between the two castes (Oettler et al ., 2019; Schultner et al ., 2023).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations